Motor Recovery After Stroke: From a Vespa Scooter Ride Over the Roman Sampietrini to Focal Muscle Vibration (fMV) Treatment. A 99mTc-HMPAO SPECT and Neurophysiological Case Study - Toscano, Massimiliano; Ricci, Maria; Celletti, Claudia; Paoloni, Marco; Ruggiero, Marco; Viganò, Alessandro; Jannini, Tommaso B.; Altarocca, Alberto; Liberatore, Mauro; Camerota, Filippo; Di Piero, Vittorio (Frontiers in Neurology, 2020)
Focal repetitive muscle vibration (fMV) is a safe and well-tolerated non-invasive brain and peripheral stimulation (NIBS) technique, easy to perform at the bedside, and able to promote the post-stroke motor recovery through conditioning the stroke-related dysfunctional structures and pathways. Here we describe for the first time the concurrent cortical and spinal plasticity induced by fMV in a chronic stroke survivor, as assessed with 99mTc-HMPAO SPECT, peripheral nerve stimulation, and gait analysis. A 72-years-old patient was referred to our stroke clinic for a right leg hemiparesis and spasticity resulting from a previous (4 years before) hemorrhagic stroke. He reported a subjective improvement of his right leg’s spasticity and dysesthesia that occurred after a 30-minutes ride on a Vespa scooter as a passenger over the Roman Sampietrini (i.e. cubic-shaped cobblestones). Taking into account both the patient’s anecdote and the current guidelines that recommend fMV for the treatment of post-stroke spasticity, we then decided to start fMV treatment. 12 fMV sessions (frequency 100 Hz; amplitude 0.2-0.5 mm, three 10-minute daily sessions per week for 4 consecutive weeks) were applied over the quadriceps femoris, triceps surae, and hamstring muscles through a specific commercial device (Cro®System, NEMOCOsrl). A standardized clinical and instrumental evaluation was performed before (T0) the first fMV session and after (T1) the last one. After fMV treatment, we observed a clinically relevant motor and functional improvement, as assessed by comparing the post-treatment changes in the score of the Fugl-Meyer assessment, the Motricity Index score, the gait analysis, and the Ashworth modified scale, with the respective minimal detectable change at the 95% confidence level (MDC95). Data from SPECT and peripheral nerve stimulation supported the evidence of a concurrent brain and spinal plasticity promoted by fMV treatment trough activity-dependent changes in cortical perfusion and motoneuron excitability, respectively. In conclusion, the substrate of post-stroke motor recovery induced by fMV involves a concurrently acting multisite plasticity (i.e. cortical and spinal plasticity). In our patient, operant conditioning of both cortical perfusion and motoneuron excitability throughout a month of fMV treatment was related to a clinically relevant improvement in his strength, step symmetry (with reduced limping), and spasticity.